Supply chain performance measurement: case evidence from a Malaysian automotive manufacturer - Syed Abdul Hamid, Sharifah Fadzlon; Kasim, Eley Suzana; Rajamanoharan, Indra Devi; Omar, Normah (2011)
Over the past two decades, organizations have understood that various business improvement methodologies need to be adopted in order to compete successfully. More importantly, businesses seek to capitalize on their supply chain resources and capabilities as a way to achieve sustainable competitive advantage (Kurien & Qureshi, 2011; Paulraj & Chen, 2007). The supply chain concept is based on the premise that products and services reaching the final customers are the result of cumulative effort of multiple business organizations linked together in the provision of those goods. Thus the supply chain typically consists of suppliers, manufacturers, warehouse facilities, distributors and finally, the end customers (Simchi-Levi, Kaminsky & Simchi-Levi, 2003; Chopra & Meindl, 2001). It is through the effective management of the strengths and weaknesses of these supply chain members through supply chain management (SCM) that businesses are able to maximize customer value (Jesperson & Skjott-Larsen, 2005). Supply chain management (SCM) emphasizes on increasing efficiency, reducing lead times and consequently, on minimizing inventory and costs (au et aI, 2010), all of which aim at improving operational performance. These goals are particularly vital for companies competing in the automobile industry, the focus of this research. The Toyota Production System (TPS) implemented in most automobile companies, including in Malaysia, provide a unique lean approach to car manufacturing that emphasizes on attaining these objectives. TPS advocates the leveraging of such operational excellence in achieving competitive advantage, which inherently requires effective management of their supply chains (Liker, 2004). The enhanced operational performance is based partly on supply chain tools and methods such as Just-In-Time (JIT) technique, kaizen, and one-piece flow approach as well as building supplier relationship. Studies have suggested that these techniques could improve supply chain performance of automotive firms (e.g. Nordin, Md Deros & Abd Wahab, 2010, Lockstrom, Schadel, Harrison, Moser & Malhotra, 2008). However, little empirical research has been conducted to examine, in particular, on how the performance of the automotive supply chain is evaluated.